The Notary Legal Protection in Criminal Cases Related to Authentic Fiduciary Deeds - Adillah, Mokhamad Hussain (TABELLIUS: Journal of Law, 2023)
Criminal cases related to authentic fiduciary deed can position the notary as a witness, suspect and even the accused which shows that the notary has no legal immunity. This research is about Legal Protection of Notaries in Criminal Cases Related to Authentic Fiduciary Deeds, which aims to find out and analyze the position of notaries in criminal cases related to the fiduciary deed they made and their legal protection. This study uses a sociological juridical approach. Data collection was carried out through interviews and literature study. Data analysis was carried out in a qualitative descriptive manner. This research shows that a notary in a criminal case related to a fiduciary deed he made can serve as a witness or perpetrator of a crime as stipulated in Article 35 of Act No. 42/1999 concerning Fiduciary Guarantees.participating in criminal acts (Article 55 of the Criminal Code), assisting perpetrators in committing crimes (Article 231 of the Criminal Code), making fake letters (Article 263 of the Criminal Code), providing false statements in authentic deeds (Article 266 of the Criminal Code), embezzlement (Article 372 of the Criminal Code), and fraud (Article 378 of the Criminal Code) which causes harm to other parties, the notary can be held criminally responsible.Legal protection for notaries in criminal cases related to the fiduciary deed he made namelyafter the issuance of the Constitutional Court decision No. 49/PUU-X/2012 namely the summons of a notary through the Notary Honorary Council according to Article 66 UUJN. In addition, notaries still receive protection from the rights and obligations of notary disobeying as referred to in Article 1909 paragraph (3) of the Civil Code and Article 322 of the Criminal Code. Keywords: Criminal; Fiduciary; Protection.